Education to Parents About "The Secret of Healthy Children: Starting With Safe Drinking Water" at the Ponrang Public Health Center, Luwu District - Isna Arista; Zamli; Sudirman Sanuddin (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Background: Safe drinking water is the main foundation in maintaining health, especially for children who are in the growth and development phase and are very vulnerable to disease exposure. Healthy children are not only the result of nutritious food intake, but also depend heavily on the quality of drinking water consumed every day. Safe drinking water is the main foundation in maintaining health, especially for children who are in the growth and development phase and are very vulnerable to disease exposure. In the working area of the Ponrang Community Health Center, Luwu Regency, there are still parents who do not understand the importance of safe drinking water for children's health. This community service activity aims to increase parental awareness about the importance of safe and clean drinking water in supporting children's health and growth, as well as explaining the health risks that can arise from consuming unhygienic water. The method used is interactive counseling accompanied by discussions and distribution of educational media such as leaflets. The results of the activity showed an increase in participants' knowledge regarding safe drinking water, the dangers of unsafe drinking water, the characteristics of healthy children, and practical tips for parents at home. In conclusion, appropriate and locally-based education can increase parents' understanding and awareness in maintaining the quality of their children's drinking water, which contributes to improving the overall health of the family.